PERAN ORANG TUA DALAM MENDUKUNG KARAKTER KEDISIPLINAN DAN TANGGUNG JAWAB PADA ANAK USIA DINI - Nurhidayati Nurhidayati; Dian Kristiana; Nurtina Irsad Rusdiani (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to describe the role of parents in supporting the development of discipline and responsibility character in early childhood, as well as to present the outcomes of children's behavior shaped through such habituation. The research employs a qualitative approach with a case study design involving 10 children aged 5–6 years at TK Dharma Wanita Bringinan and their parents. Data were collected through observation, in-depth interviews, and documentation. The data analysis techniques used include data reduction, data presentation, and drawing conclusions. The findings reveal that parents play a significant role in fostering discipline and responsibility in young children through three main aspects: habitual routines, role modeling, and positive communication. Children who are consistently exposed to disciplined routines at home demonstrate orderly behavior at school, such as organizing stationery, completing tasks on time, and respecting classroom rules. Responsibility is also reflected in behaviors such as taking care of personal belongings, helping the teacher, and admitting mistakes. This success is supported by active parental involvement and collaboration with teachers.Thus, the role of parents is not only as supporters but also as the primary foundation in shaping children to become disciplined, responsible, and prepared to face future challenges